The tobacco industry's accounts of refining indirect tobacco advertising in Malaysia. (24th November 2004) - Assunta, M; Chapman, S
Abstract : Objective: To explore tobacco industry accounts of its use of indirect tobacco advertising and trademark diversification (TMD) in Malaysia, a nation with a reputation for having an abundance of such advertising. Methods: Systematic keyword and opportunistic website searches of formerly private tobacco industry internal documents made available through the Master Settlement Agreement. Results: 132 documents relevant to the topic were reviewed. TMD efforts were created to advertise cigarettes after advertising restrictions on direct advertising were imposed in 1982. To build public credibility the tobacco companies set up small companies and projected them as entities independent of tobacco. Each brand selected an activity or event such as music, travel, fashion, and sports that best suited its image. RJ Reynolds sponsored music events to advertise its Salem brand while Philip Morris used Marlboro World of Sports since advertising restrictions prevented the use of the Marlboro man in broadcast media. Despite a ban on tobacco advertisements in the mass media, tobacco companies were the top advertisers in the country throughout the 1980s and 1990s. The media's dependence on advertising revenue and support from the ruling elite played a part in delaying efforts to ban indirect advertising. Conclusion: Advertising is crucial for the tobacco industry. When faced with an advertising ban they created ways to circumvent it, such as TMDs.